Evaluation of different criteria for blood donor deferral in a hospital affiliated with teaching institute - Dr. Mayur J Kokani; Dr. Chiragkumar B. Menapara (Tropical Journal of Pathology and Microbiology, 2019)
Objective: The only objective of our present study is evaluation of the rate and major reasons of blood donor deferrals in our institute.Materials and Methods: A retrospective study was done at the blood bank, GMERS Medical College & Hospital, Junagadh (Gujarat) over a period of 4 years from January 2015 to December 2018. Donor eligibility criteria were followed according to the National guidelines for blood donation. Donors deferred were analysed according to their age, sex, type of donor, type of deferral, and reasons for deferral.Result: Of 26610 blood donors, 98.07% were eligible for donation and 1.93% were deferred. The deferral rates among male population and female population were 1.32% and11.92% respectively. Temporary deferral was more common than permanent one (52.92% vs 47.08%). Leading causes of deferral were hypertension (40.08% cases), anemia (21.98% cases) and hypotension (14.40% cases). Anemia was the commonest cause for temporary deferral, whereas hypertension was the commonest for permanent deferral. Maximum number of deferrals were observed in the age group of 36–50 years (41.25% cases).Conclusion: Rejection or Deferral play a pivot role in good and healthy donor selection. Both temporary and permanent criteria must be kept in mind while pre-transfusion screening of a blood donor. Inappropriate selection and unnecessary deferral are always hazardous in transfusion medicine, because both of them reduce the availability of healthy blood donors.